‘I Can Teach English More Confidently’: How Madrassas’ and Pesantrens’ English Teachers Perceived ELTT Program - Asfihana, Raida; Sari, Afifah Linda; Hasanah, Amalia; Setiowati, Ning (Journal of English Education and Teaching, 2023)
The study sought to investigate the perception of English teachers in madrassas and pesantrens toward the English Language Teacher Training (ELTT) program they underwent for five months. A convergent mixed-method research design was used, comprising a set of questionnaires administered to thirty-two teachers across three cities, namely Banjarmasin, Metro, and Palembang. Subsequently, interviews were conducted with twelve teachers who participated in the study. Interactive data analysis was employed to analyze the results obtained from the questionnaires and interviews. The study found that numerous teachers reported receiving significant benefits in their teaching and learning skills after participating in the ELTT program, including a boost in self-esteem when delivering English language instruction and enhanced English teaching abilities. However, participants also highlighted internet connectivity and time management as major hurdles that required attention. Hence, it is recommended that the Ministry of Religious Affairs continues to implement the program since it provides teachers with opportunities to enhance their English teaching skills. Consequently, this will enable students to receive greater exposure to the English language, facilitating their learning process.